2008
DOI: 10.1111/j.1095-8312.2007.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Sex versus parasitism versus density

Abstract: The Red Queen hypothesis predicts that sexual reproduction should be favoured when the risk of infection by parasites is high. However, this prediction may also be achieved independently by means of the reproductive assurance and the density-dependent transmission hypotheses because higher densities increase the chances of fertilization (i.e. mates are easier to find) and increase the risk of infection. Additionally, the Red Queen hypothesis makes a long-term prediction that infection should be genotype-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…We indeed found that infection prevalence is significantly correlated with the observed variation in clonal diversity of M. tuberculata populations. Consistent with previous work (Heller & Farstey, ; Ben‐Ami & Heller, , , ), we found no relationship between infection prevalence and male frequency. Furthermore, snail density could neither explain the variation in host clonal diversity nor explain the variation in male frequency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We indeed found that infection prevalence is significantly correlated with the observed variation in clonal diversity of M. tuberculata populations. Consistent with previous work (Heller & Farstey, ; Ben‐Ami & Heller, , , ), we found no relationship between infection prevalence and male frequency. Furthermore, snail density could neither explain the variation in host clonal diversity nor explain the variation in male frequency.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, sex in M. tuberculata plays a crucial role in its ability to invade new ecosystems, because it amplifies the effect of multiple introductions of the snail by generating novel trait combinations (Facon et al ., , ). The frequency of fertile males can reach up to 66% particularly in Israel (Livshits & Fishelson, ; Heller & Farstey, ; Hodgson & Heller, ; Ben‐Ami & Heller, , , ).…”
Section: Methodsmentioning
confidence: 99%
“…Female M. tuberculata usually reproduce parthenogenetically (obligate apomixis) [ 23 25 ], but also via sporadic sexual reproduction in the presence of males [ 26 ]. In Israel, the frequency of fertile males can reach up to 66% [ 21 , 27 – 30 ]. Furthermore, sex plays a crucial role in the ability of M. tuberculata to invade new ecosystems, because it amplifies the effect of multiple introductions of the snail by generating novel trait combinations [ 31 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…This, however, only challenges the universality of the red-queen theory. (See Brown et al (1995); Hanley et al (1995); Vernon et al (1996); Weeks (1996); Ben-Ami & Heller (2005; 2008); Tobler & Schlupp (2005); Killick et al (2008); Kotusz et al (2014) for evidence on exceptions to red-queen predictions. )…”
Section: Introductionmentioning
confidence: 99%